Spirals visualizing unseen energies through an immersive installation - Espinosa, Danna Mhae Buenavista; Feleo, Roberto; Sta Ana, Mary Catherine (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Artmaking can be viewed as a spiritual practice and activity; a way to contemplate and visually express metaphysical beliefs that cannot always be verbally communicated or reasoned. Similarly, my personal intention is to visually present an alternative approach to looking at reality.

The thesis is an exploration in visualizing subtle energies around us. Using spirals, I intend to visually represent the dynamic subtle energies which nurture and sustain life. The spiral's movement is observed in many patterns of growth: in the form of embryos, horns, whirlpools, hurricanes and galaxies. The use of the Fibonacci spiral as form of the installation is to mimic the natural energetic pattern of growth observed in many forms of creation. I am also using the symbolic meaning of colors; particularly the rainbow spectrum colors which represent the characteristics and vibrations of the divine energy forces which shape life. The approaches I employed are reflective of the intention to create a space that will hopefully invite healing and contemplation.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaves 20-21
Keywords: Spirals; Subtle energies; Healing space; Installations (Art)